The social construction of leadership studies: Representations of rigour and relevance in textbooks. (April 2018) - Carroll, Brigid; Firth, Josh; Ford, Jackie; Taylor, Scott
Considerations of rigour and relevance rarely acknowledge students, learning or the textbooks many of the academic community use to frame education. Here we explore the construction of meaning around rigour and relevance in four leadership studies textbooks – the two most globally popular leadership textbooks and two recent additions to the field – to explore how these ideas are represented. We read the four texts narratively for structure, purpose, style and application. We further embed the analysis by considering the cultural positioning of the textbook-as-genre within leadership studies as a field more generally. This exploration of the textbook raises critical questions about rigour, relevance and the relationship constructed between them. From this, we argue for a re-commitment to the genuine 'text-book' written to engage students in understanding leadership as a continuing conversation between practices, theories and contexts, rather than as a repository of rigorous and/or relevant content that lays claim to represent an objective science of leadership studies.